miRNome profiling of clonal stem cells in Ph+ CML - Ruiz, María Sol (2020)
Chronic myeloid leukemia (CML) is a myeloid stem cell neoplasm characterized by an expansion of myeloid progenitor cells and the presence of BCR-ABL1 oncoprotein. Since the introduction of specific BCR-ABL1 tyrosine kinase inhibitors (TKI), overall survival has improved significantly. However, under long-term therapy patients may have residual disease that originates from TKI-resistant leukemic stem cells (LSC). In this work, we analyzed the miRNome of CML LSC, normal hematopoietic stem cells (HSC) obtained from the same CML patients, and stem and progenitor cells obtained from healthy donors (HD) by next-generation sequencing. We detected a global decrease of microRNA levels in LSC and HSC from CML patients, and decreased levels of microRNAs and snoRNAs from a genomic cluster in chromosome 14, suggesting a mechanism of silencing of multiple non-coding RNAs. Surprisingly, HSC from CML patients, despite the absence of BCR-ABL1 expression, showed an altered miRNome. In silico analysis revealed an association between validated microRNAs and multiple metabolic pathways, suggesting that these molecules may be mediators of the previously reported dysregulation of LSC metabolism. This is the first report of the LSC miRNome that distinguishes between BCR-ABL1+ LSC and their BCR-ABL1- counterparts, providing valuable data for future studies.